2017
DOI: 10.1175/jcli-d-16-0557.1
|View full text |Cite
|
Sign up to set email alerts
|

How Well Are Tropical Cyclones Represented in Reanalysis Datasets?

Abstract: Tropical cyclones (TCs) are identified and tracked in six recent reanalysis datasets and compared with those from the IBTrACS best-track archive. Results indicate that nearly every cyclone present in IBTrACS over the period 1979–2012 can be found in all six reanalyses using a tracking and matching approach. However, TC intensities are significantly underrepresented in the reanalyses compared to the observations. Applying a typical objective TC identification scheme, it is found that the largest uncertainties i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
287
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 232 publications
(329 citation statements)
references
References 72 publications
18
287
2
1
Order By: Relevance
“…Therefore, the increased number of detections using the OWZP detection scheme may be due to the more favorable large‐scale climate of the ACCESS model. The reduced number of detections in the reanalysis using the CSIRO scheme is due to a resolution‐dependent 10 m wind speed threshold, which causes an underestimation of TC numbers in the low‐resolution reanalysis data sets (Hodges et al, ; Murakami, ). The resolution‐dependent (CSIRO) TC tracking scheme has better performance in the high‐resolution ACCESS model compared to the lower resolution reanalysis; we speculate that the model has improved the simulation of TC intensity compared with the reanalysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the increased number of detections using the OWZP detection scheme may be due to the more favorable large‐scale climate of the ACCESS model. The reduced number of detections in the reanalysis using the CSIRO scheme is due to a resolution‐dependent 10 m wind speed threshold, which causes an underestimation of TC numbers in the low‐resolution reanalysis data sets (Hodges et al, ; Murakami, ). The resolution‐dependent (CSIRO) TC tracking scheme has better performance in the high‐resolution ACCESS model compared to the lower resolution reanalysis; we speculate that the model has improved the simulation of TC intensity compared with the reanalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, compared to the earlier reanalysis versions, the ERA-Interim has improved model physics and includes the use of four-dimensional variational data assimilation (Compo et al, 2011;Dee et al, 2011). Recent studies showed that TC intensity is underestimated in the ERA-Interim reanalysis compared to the observations (Hodges et al, 2017;Murakami, 2014).…”
Section: Observational and Era-interim Datamentioning
confidence: 99%
“…This is done using an objective feature tracking method that tracks all tropical systems through their full life cycles and then matches the tracks against those of IBTrACS to identify the identically same tropical cyclones (TCs); a full description of the tracking and matching methodology is given in Hodges et al . (). This has the benefit of identifying more of the TC life cycle, such as the part before the system is declared a TC and also after it is no longer followed by the operational observing centres.…”
Section: Methodsmentioning
confidence: 97%
“…The tracking algorithm described by Hodges () was applied using a methodology based on Hodges et al (), who use TRACK to identify tropical cyclones, as well as their antecedent and subsequent phases as tropical lows and tropical depressions. This was deemed appropriate since the southern African tropical lows are similar in spatial extent and magnitude to tropical lows which transition into and out from tropical cyclones.…”
Section: Methodsmentioning
confidence: 99%